Constructed Wetlands for Industrial Wastewater Treatment 2018
DOI: 10.1002/9781119268376.ch17
|View full text |Cite
|
Sign up to set email alerts
|

Removal Processes of Pharmaceuticals in Constructed Wetlands

Abstract: acidic conditions 166 acidification 158 acid mine drainage (AMD) 249-255 acidogenesis 134 acidogenic phase 267 acid rock drainage (ARD) 249 acid volatile sulfides and simultaneously extracted metals (AVS-SEM) 237

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 278 publications
0
22
0
Order By: Relevance
“…Several studies have found that TWs can partly remove organic micropollutants, in some cases more effectively than conventional WWTPs [25,54]. Therefore, TWs have been installed to treat wastewater from pharmaceuticals and cosmetics industry [11] besides other municipal and industrial effluents. To ensure food safety when irrigating crops with reclaimed water treated by NBS, further research could investigate the design requirements of technologies and the combination within the treatment system to effectively remove organic micropollutants and other potentially harmful substances such as microplastics and heavy metals.…”
Section: Area Requirements and Integration Into The Urban Infrastructurementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have found that TWs can partly remove organic micropollutants, in some cases more effectively than conventional WWTPs [25,54]. Therefore, TWs have been installed to treat wastewater from pharmaceuticals and cosmetics industry [11] besides other municipal and industrial effluents. To ensure food safety when irrigating crops with reclaimed water treated by NBS, further research could investigate the design requirements of technologies and the combination within the treatment system to effectively remove organic micropollutants and other potentially harmful substances such as microplastics and heavy metals.…”
Section: Area Requirements and Integration Into The Urban Infrastructurementioning
confidence: 99%
“…Alongside end-of-pipe technologies to recover nitrogen and phosphorus at conventional wastewater treatment plants (WWTPs), such as mono-incineration for phosphorus recovery, a range of nature-based solutions (NBS) for wastewater treatment can be applied to recover water, nutrients, materials, and energy, including the production of irrigation water and nutrients from domestic wastewater for safe reuse in urban and peri-urban agriculture [27]. NBS are robust, resilient technologies and can treat wastewater with minimal chemical and energy footprints, including the effective removal of a range of organic micropollutants [11,25,54]. If integrated into the built environment of a city, they can provide multiple benefits of vegetation and ecosystems, such as reducing urban heat islands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their good removal efficiency is commonly recognized in terms of organic matter, nutrients and metals (Haberl et al 2003;Vymazal 2007;Vymazal and Kr€ opfelov a 2015). In the last decades, the potential of CWs to remove other emergent pollutants like PhACs has also demonstrated their good potential (Verlicchi and Zambello 2014;Carvalho et al 2014;Lv et al 2016;Dordio and Carvalho 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They are known for being tolerant to flooded soils and polluted waters, being therefore suitable for phytoremediation Wang et al 2014). They already demonstrated their capacity for removing pollutants such as nutrients, organic matter and metals (Gomes et al 2014;Di Luca et al 2015;Ediviani et al 2018;Huang et al 2018), and, more recently, also their potential to remove some PhACs (Mackul'Ak et al 2015;Dordio and Carvalho 2018) although, in the latter case, the mechanisms involved in the removal of such pollutants are not so well characterized.…”
Section: Introductionmentioning
confidence: 99%